C reactive protein and chronic obstructive pulmonary disease: a Mendelian randomisation approach - Morten Dahl; Jørgen Vestbo; Jeppe Zacho; Peter Lange; A. Tybjaerg-Hansen; Børge G. Nordestgaard (2010)
Background It is unclear whether elevated plasma C reactive protein (CRP) is causally related to chronic obstructive pulmonary disease (COPD). The authors tested the hypothesis that genetically elevated plasma CRP causes COPD using a Mendelian randomisation design. Methods The authors measured high-sensitivity CRP in plasma, genotyped for four single nucleotide polymorphisms in the CRP gene, and screened for spirometry-defined COPD and hospitalisation due to COPD in 7974 individuals from the Copenhagen City Heart Study and in 32 652 individuals from the Copenhagen General Population Study. Results Elevated plasma CRP >3 mg/l compared with <1 mg/l was associated with risk estimates of 1.8 and 2.8 for spirometry-based COPD and of 1.6 and 1.8 for hospitalisation due to COPD in the Copenhagen City Heart Study and the Copenhagen General Population Study, respectively. Genotype combinations of the four CRP polymorphisms were associated with up to a 62% increase in plasma CRP. However, these genotype combinations did not associate with increased risk of COPD or hospitalisation due to COPD in either cohort or in the two cohorts combined. On instrumental variable analysis, a doubling of plasma CRP versus a doubling of genetically elevated CRP resulted in ORs for COPD of 1.27 (95% CI 1.25 to 1.30) versus 1.01 (0.81 to 1.26) and for COPD hospitalisation of 1.47 (1.43 to 1.51) versus 0.82(0.59 to 1.13). Conclusion Although elevated CRP is related to both a diagnosis of COPD and subsequent hospital admission, genetically elevated plasma CRP is not associated with an increased risk of clinical COPD. This suggests that the association between CRP levels and COPD is not causal.